New data on the distribution of digger wasps of the genus Ammophila W. Kirby, 1798 (Hymenoptera, Sphecidae) - Baghirov, R. T.-o; Nesterovich, A. A. (Acta Biologica Sibirica, 2019)
An annotated list is given and the distribution of five species of digger wasps genus Ammophila, collected in the circumpolar regions of Western Siberia (in the Yamalo-Nenets Autonomous District) in 2017, is specified.